Revealing the Effect of Big Data Capabilities on Efficiency-Based Business Model Innovation - Liang Botao; Chuleerat Kongruang (Ital Publication, 2024)
Objectives: Business model innovation is significant for corporation performance. Unclear or poorly designed business models can only achieve moderate or insignificant results in terms of performance. Under the view of innovation theory, multiple factors affect the efficiency-based business model innovation. Big data capabilities, knowledge creation, and Institutional environment are proposed. Methods: With the collection from 513 pig farming enterprises in China, this research analyzes the relationships among big data capabilities, knowledge creation, institutional environment, and efficiency-based business model innovation by SMART-PLS. Findings: As a result, big data capabilities have a positive impact on efficiency-based business model innovation. Big data capabilities have a positive impact on knowledge creation. Knowledge creation has a positive impact on efficient business model innovation, which is supported. Knowledge creation mediates between big data capabilities and efficient business model innovation, which is supported. The impact of institutional environment regulation knowledge creation on efficient business model innovation. Novelty:This research has theoretical and practical contributions. This study implies the theory of innovation to the practice. And it also enriches the literature and research on business model innovation. Doi: 10.28991/ESJ-2024-08-04-016 Full Text: PDF